Patient care under uncertainty - Manski, Charles F. (New Jersey Princeton university press, 2019)
How can cutting-edge economics improve decision-making methods for doctors? Although uncertainty is a common element of patient care, it has largely been overlooked in research on evidence-based medicine. Patient Care under Uncertainty strives to correct this glaring omission. Applying the tools of economics to medical decision making, Charles Manski shows how uncertainty influences every stage, from risk analysis to treatment, and how this can be reasonably confronted.
Keywords: Medicine Decision making; Medical economics; Economics, Medical